1998
DOI: 10.1074/jbc.273.16.9602
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the Role of His-143 in the Mechanism of Type I Dehydroquinase from Escherichia coli Using Two-dimensional1H,13C NMR

Abstract: Type I dehydroquinase from the shikimate pathway of Escherichia coli dehydrates dehydroquinate to dehydroshikimate. pH/log V max profiles of the enzyme indicate the presence of a single ionizing group with a pK a of 6.2. Chemical modification experiments with diethyl pyrocarbonate have identified the conserved residue His-143 as essential for catalysis in this enzyme and the pK a for this modification is also 6.2, implying that this is the single ionizing residue in dehydroquinase that may be acting as a gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The nearby E142 could elevate basicity of H144 by forming a hydrogen bond to NE2 of H144, improving its proton abstraction ability. Histidine functions as a base for initial proton removal during many enzymatic reactions, including some type I 3-dehydroquinate dehydratases (23,24). Furthermore, although the activity of a H175A mutant is attenuated, the adjacent AsbF H144A mutant is completely inactive.…”
Section: Structural Characterization Of Asbf Bound To Its Product 3mentioning
confidence: 99%
“…The nearby E142 could elevate basicity of H144 by forming a hydrogen bond to NE2 of H144, improving its proton abstraction ability. Histidine functions as a base for initial proton removal during many enzymatic reactions, including some type I 3-dehydroquinate dehydratases (23,24). Furthermore, although the activity of a H175A mutant is attenuated, the adjacent AsbF H144A mutant is completely inactive.…”
Section: Structural Characterization Of Asbf Bound To Its Product 3mentioning
confidence: 99%
“…On the basis of pH/log V max profiles [15] and the pK a value from diethyl polycarbonate treatment [16], a single ionizing group was measured with a pK a value of 6.2 and therefore postulated to be His143 residue. However, the pH titration indicated that His143 does not ionize over the pH range of 6-9.5 in the presence and absence of the binding substrate [17], and so cannot possess the pK a value of 6.2. Thus, the ionization observed with the pK a value of 6.2 should be associated with a neighboring residue of His143.…”
Section: Determination Of Ionization Statesmentioning
confidence: 94%
“…This enables the nucleophilic attack on the carbonyl carbon atom in the substrate by Lys170 residue. Furthermore, the K170A mutant does not affect the isoelectric point of the enzyme [17], meaning that Lys170 residue is likely uncharged. This supports that Lys170 is deprotonated with the low pK a value of 6.2 and is also in good agreement with the previously proposed mechanism [9].…”
Section: Determination Of Ionization Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 His143 is involved in Schiff base formation/hydrolysis, but its subsequent involvement in the dehydratation is uncertain. 42 Met23 and Met205 have also been identified as active site residues (near to the carboxylate of the substrate) although their role in substrate binding or catalysis has not yet been established. 43 …”
Section: A Type I Dehydroquinasementioning
confidence: 99%